Neonatal and Paediatric Heart and Renal Outcomes Network: design of a multi-centre retrospective cohort study. (20th May 2019) - Gist, Katja M.; Blinder, Joshua J.; Bailly, David; Borasino, Santiago; Askenazi, David J.; Cooper, David S.; Krawczeski, Catherine D.; Gaies, Michael; Morales, David L. S.; Hock, Kristal M.; Alten, Jeffrey
Abstract: Background: Cardiac surgery-associated acute kidney injury is common. In order to improve our understanding of acute kidney injury, we formed the multi-centre Neonatal and Pediatric Heart and Renal Outcomes Network. Our main goals are to describe neonatal kidney injury epidemiology, evaluate variability in diagnosis and management, identify risk factors, investigate the impact of fluid overload, and explore associations with outcomes. Methods: The Neonatal and Pediatric Heart and Renal Outcomes Network collaborative includes representatives from paediatric cardiac critical care, cardiology, nephrology, and cardiac surgery. The collaborative sites and infrastructure are part of the Pediatric Cardiac Critical Care Consortium. An acute kidney injury module was developed and merged into the existing infrastructure. A total of twenty-two participating centres provided data on 100–150 consecutive neonates who underwent cardiac surgery within the first 30 post-natal days. Additional acute kidney injury variables were abstracted by chart review and merged with the corresponding record in the quality improvement database. Exclusion criteria included >1 operation in the 7-day study period, pre-operative renal replacement therapy, pre-operative serum creatinine >1.5 mg/dl, and need for extracorporeal support in the operating room or within 24 hours after the index operation. Results: A total of 2240 neonatal patients were enrolled across 22 centres. The incidence of acute kidney injury was 54% (stage 1 = 31%, stage 2 = 13%, and stage 3 = 9%). Conclusions: Neonatal and Pediatric Heart and Renal Outcomes Network represents the largest multi-centre study of neonatal kidney injury. This new network will enhance our understanding of kidney injury and its complications.